Nodular lesions in diabetic nephropathy: Collagen staining and renal prognosis. (May 2017) - Mise, Koki; Ueno, Toshiharu; Hoshino, Junichi; Hazue, Ryo; Sumida, Keiichi; Yamanouchi, Masayuki; Hayami, Noriko; Suwabe, Tatsuya; Hiramatsu, Rikako; Hasegawa, Eiko; Sawa, Naoki; Fujii, Takeshi; et al.
Highlights: Faintly-PAS/PAM stained nodular lesions were seen in 61% of all patients. The lesions were named mesangiolytic nodular lesions (MNL) based on the pathogenesis. Type IV collagen is negative, but type V and VI collagen were positive in MNLs. The presence of MNLs was independently associated with higher HR for ESRD. MNLs should probably be investigated in all patients with nodular lesions. Abstract: Aims: Nodular lesions are one of the most characteristic pathological changes of advanced diabetic nephropathy (DN). Previous studies have demonstrated that the pattern of both routine and collagen staining of nodular lesions changes during their development. However, the association between such changes of staining and the renal prognosis remains unclear. Methods: Among 252 patients with biopsy-proven DN, 67 met the selection criteria and were enrolled to investigate this relationship. In all patients, nodular lesions were stained with periodic acid Schiff, periodic acid methenamine silver, and Masson trichrome stains, and immunostaining was done for type I, III, IV, V, and VI collagen. The endpoint was commencement of dialysis due to end-stage renal disease. Results: At least one mesangiolytic nodular lesion (MNL) that showed faint staining for PAS and PAM was found in 61% of the patients. MNLs were negative for type IV collagen staining, unlike the strong positivity of non-MNLs, while type V and VI collagen staining were strongly positive in all nodular lesions. Cox proportional hazards regression analysis revealed that the hazard ratio (HR) for the endpoint was significantly higher in patients with at least one MNL than in patients with no MNLs after adjustment for known promoters of renal progression (HR: 2.94; 95% confidence interval: 1.24–7.07). Conclusions: MNLs may reflect characteristic differences of collagen production and could be a useful prognostic indicator in patients with nodular lesions. Further investigation of the mechanism underlying these differences of collagen production could contribute to finding new therapeutic targets for DN.